Language Function by The Main Character in œThe Last of Us Part 2 Video Games - Mustika, Alda; Gintings, Immanuel Prasetya; Natsir, Muhammad (TRANSFORM: Journal of English Language Teaching and Learning, 2023)
This study was conducted by using descriptive qualitative method. It was concerned with the description of data in the form of utterances by the main character in The Last of us part 2 Video Game (2020). In conducting this research, the researcher (1) found out the types of language function in The Last of us part 2 Video Games. (2) described the realization types of language function in The Last of us part 2 Video Games. In the application of the language function, the last of us part 2 video games utterances used Jakobson™s theory. The result showed first, that most dominant type of language function in Jakobson™s theory is Expressive Function with (37%). The percentage directive function is (32%). The percentage Metalinguistic function is (20%). The lowest percentage in language function that Referential function is (11%). Second, The realization of language function described, such as : Expressive Function, that is action from another character make a feeling to main character, for example : (Jesus! You almost gave me heart attack, Fuck!, Gotcha!!, Just banged up!), Directive Function, is about attempt to get someone to do something. For example: (You better run little shit1, Run Dina!, No!, okay!), Referential function, is the communication of information, for example (oh, there™s the ski lodge, that™s the one on Tommy and Joel™s route), Metalinguistic function explain about the answer is code itself, for example: (just another evacuated neighborhood).